Measurement of climate change-related food (in)security and food sovereignty in Canada’s northern communities and the circumpolar region: a scoping review protocol - Tracey Galloway; Iva Seto; Nicholas Worby; Joanna Szurmak; David Gerstle; Rebecca Tough (BMJ Open)
Introduction Climate change impacts the circumpolar region (including northern Canada) at a greater magnitude than other parts of the world. This affects food (in)security as well as food sovereignty. This scoping review aims to map the methods of measuring food (in)security and food sovereignty across northern Canada and the circumpolar region in support of the Yukon Government’s climate change adaptation strategy.Methods and analysis We will adhere to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews, and work will be conducted according to the Joanna Briggs Institute (JBI) manual chapter on scoping reviews. Academic librarians develop the academic literature and grey literature search strategies, and the search strategies are further revised through iterative stages of peer review. The search strategy includes 7 academic literature databases, 11 grey literature databases, over 50 websites and the University of Toronto Libraries catalogue. Covidence, an evidence synthesis software, will be used for screening and extraction. The extraction chart will be developed and piloted by our team. A minimum of two reviewers will conduct screening, and conflicts will be resolved through discussion. Data will be extracted by one reviewer and verified by a second. Conflicts will be resolved through discussion or by a third reviewer.Ethics and dissemination This project does not require ethical approval as it is secondary research; data will be extracted from published academic research papers, dissertations, and publicly available reports and documents. Our dissemination plan includes presentations at conferences, submission to international peer-reviewed journals and a workshop on the search strategies.